2019
DOI: 10.1021/acs.jpclett.8b03728
|View full text |Cite
|
Sign up to set email alerts
|

Constructing the Electronic Structure of CH3NH3PbI3 and CH3NH3PbBr3 Perovskite Thin Films from Single-Crystal Band Structure Measurements

Abstract: Photovoltaic cells based on halide perovskites and possessing remarkably high power conversion efficiencies have been reported. To push the development of such devices further, a comprehensive and reliable understanding of their electronic properties is essential, but presently not available. To provide a solid foundation for understanding the electronic properties of polycrystalline thin films, we employ single crystal band structure data from angle-resolved photoemission measurements. For two prototypical pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 68 publications
4
88
3
Order By: Relevance
“…Despite such difficulties, several research groups have challenged the ARUPS measurements on the single crystal halide perovskites. [196][197][198][199][200] We herein digest the cases of the single crystal methylammonium lead triiodide (CH 3 NH 3 PbI 3 ; MAPI). † † † Lee et al reported the ARUPS results on MAPI single crystal samples obtained under various excitation photon energies in a range of 74-200 eV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite such difficulties, several research groups have challenged the ARUPS measurements on the single crystal halide perovskites. [196][197][198][199][200] We herein digest the cases of the single crystal methylammonium lead triiodide (CH 3 NH 3 PbI 3 ; MAPI). † † † Lee et al reported the ARUPS results on MAPI single crystal samples obtained under various excitation photon energies in a range of 74-200 eV.…”
Section: Resultsmentioning
confidence: 99%
“…209 Afterward, Zu et al also demonstrated the ARUPS analyses on the single crystal MAPI. 200 Their experimental conditions were similar to those of Yang et al; 199 an only apparent difference is that they cleaved the MAPI single crystal surface in a N 2 -filled glovebox, instead of in air, and the ARUPS measurements were conducted on the samples without air exposure. In this work, the ARUPS results taken along the G-% X and G-% M directions were interpreted to mainly represent the valence band dispersion in the X-M and X-R directions, respectively, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Photoemission spectroscopy typically generates non-equilibrium conditions with some degree of SPV and band flattening at semiconductor surfaces, on MHP surfaces in particular. [31][32][33] This circumstance places some uncertainty on the equilibrium surface position of E F measured via UPS. To sort out this issue in the present case, we performed KP-CPD/SPV measurements on all the films, in the dark and under controlled white light intensity.…”
Section: Understanding the Origin And Distribution Of Electronic Gap mentioning
confidence: 99%
“…This study highlights the necessity to use a logarithmic intensity scale to determine the VBM onset (with a remaining fundamental uncertainty of ≈50 meV, mostly underestimating the onset) 49b,c,52. On a separate note, ARPES allows the evaluation of the hole effective mass ( m h *) by performing a parabolic fit of the VBM at points R and M 49i,52,54. Values of 0.18 ± 0.06 m 0 at M (along X–M) and 0.50 ± 0.10 m 0 near R (along X–R).…”
Section: Ensemble Averaged Properties Influencing Solar Cell Parametersmentioning
confidence: 98%
“…The photoemission intensities are displayed in linear and logarithmic scales to highlight the variations in the onset of VBM determination. Reproduced with permission . Copyright 2019, American Chemical Society.…”
Section: Ensemble Averaged Properties Influencing Solar Cell Parametersmentioning
confidence: 99%